Koumine exerts its anti-colorectal cancer effects by disrupting the interaction between HSP90 and CDC37, thereby downregulating downstream signaling pathways - Lin, HaiLing; Bao, YuXuan; Cheng, XiTong; Zhang, ShuMing; Zhou, DanYang; Que, WanCai (Frontiers in Oncology, 2026)
BackgroundKoumine, a principal bioactive alkaloid derived from the traditional Chinese herb Gelsemium elegans, has demonstrated broad cytotoxic activity against various cancer cell lines. However, its specific anti-tumor efficacy and underlying molecular mechanisms in colorectal cancer (CRC) remain largely unexplored.MethodsWe employed an integrated strategy combining network pharmacology prediction with experimental validation. Bioinformatics analysis was conducted to identify potential targets. In vitro functional assays were performed to evaluate effects on cell proliferation, clonogenicity, apoptosis, migration, and invasion. Target engagement was confirmed by cellular thermal shift assay (CETSA), and the molecular mechanism was investigated through Western blot and co-immunoprecipitation analyses.ResultsNetwork pharmacology identified heat shock protein 90 (HSP90) as a key potential target, a finding supported by molecular docking simulations. Koumine significantly inhibited the malignant phenotypes of CRC cells. CETSA confirmed direct binding of koumine to HSP90. Mechanistically, koumine disrupted the functional interaction between HSP90 and its co-chaperone CDC37, leading to the downregulation and inactivation of critical downstream client proteins, including cyclin-dependent kinases CDK4 and CDK6.DiscussionThese findings elucidate that koumine exerts potent anti-CRC effects primarily by targeting the HSP90–CDC37 chaperone complex and inhibiting the CDK4/6–Rb signaling axis. This study provides a robust mechanistic foundation and compelling preclinical evidence for the further development of koumine as a promising therapeutic agent for colorectal cancer.